(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Probiotics are the live bacteria that help the host's health. Paraprobiotics, defined as “inactivated microbial cells (non-viable) that confer a health benefit to the consumer,” hold the ability to regulate the adaptive and innate immune systems, exhibit anti-inflammatory, anti proliferative and antioxidant properties and exert antagonistic effect against pathogens. When it comes to developing functional foods and nutraceuticals, paraprobiotics—which include non-viable microbial components or metabolites derived from beneficial bacteria—offer fascinating opportunities. Nutraceuticals and functional foods are becoming more and more popular due to the increased need for preventative health strategies. Beyond just providing a basic diet, many goods have specific health benefits that help prevent disease and enhance overall wellbeing. Numerous health-promoting benefits of paraprobiotics include immunomodulation, improved gut health, and anti-inflammatory qualities. Paraprobiotic production techniques are always changing, resulting in increased cost and efficacy effectiveness. This review paper delves into the potential of paraprobiotics in shaping the future of functional food and nutraceutical development. By exploring their diverse functionalities, production methods, mechanism of action and integration into various food matrices, the paper aims to provide a comprehensive understanding of their potential impact.